The home language environment and early language ability in rural Southwestern China - Zhang, Xinwu; Ma, Yue; Feng, Tianli; Zhang, Vincent; Wu, Xiaoyang; Li, Matthew; Li, Queenie; Thani, Zahra; Pappas, Lucy; Dill, Sarah-Eve; Rozelle, Scott (Frontiers in Psychology, 2023)
Using premier Language Environment Analysis technology to measure and analyze the home language environment, this observational study aims to describe the home language environment and child language ability, drawing on empirical data from 77 households with children aged 18–24 months from rural China. The results show large variation in measures of the home language environment and early language ability, similar to other rural Chinese samples. Results also demonstrate significant correlations between child age and the home language environment, maternal employment and the home language environment, father’s educational attainment and the home language environment, adult–child conversations and early language ability, and child vocalizations and early language ability.